Application of starch-nano zero-valent iron in catalytic electro-Fenton degradation of chemical wastewater

By using starch-nano zero-valent iron as a catalyst in chemical wastewater, the problems of high energy consumption and high iron sludge in the prior art are solved, and the organic pollutants in chemical wastewater are efficiently removed and material costs are reduced.

CN119774721APending Publication Date: 2025-04-08GUANGDONG UNIV OF PETROCHEMICAL TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411929431.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing electric Fenton technology has problems such as high energy consumption, slow H2O2 generation efficiency, and high iron sludge production when treating chemical wastewater.

Method used

Starch-nano-zero-valent iron (S-nZVI) is used as a catalyst to degrade chemical wastewater through Fenton oxidation reaction. The method includes adding starch-nano-zero-valent iron to chemical wastewater and optimizing the reaction effect by controlling reaction conditions such as pH and current.

Benefits of technology

The removal rate of COD is improved, the degradation effect of difficult-to-degrade organic pollutants is enhanced, and S-nZVI can be reused, reducing material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774721A_ABST
    Figure CN119774721A_ABST
Patent Text Reader

Abstract

The invention discloses application of starch-nano zero-valent iron in catalytic electro-Fenton degradation of chemical wastewater. According to the invention, a starch / nano zero-valent iron catalyst (S-nZVI) and a bare nano zero-valent iron catalyst (nZVI) are prepared by a liquid phase reduction method, and characterization analysis results show that S-nZVI has a better dispersion effect than nZVI. And under the optimal operation condition, the removal rate of COD (Chemical Oxygen Demand) can reach 76.03%. An ultraviolet-visible spectrum and a three-dimensional fluorescence spectrum are used for analyzing the wastewater before and after the reaction, and the S-nZVI catalytic electro-Fenton reaction can effectively remove benzene rings, unsaturated aldehydes, ketones, cyclic aromatic compounds and other organic pollutants in the wastewater. Experimental results show that the electro-Fenton system constructed by the S-nZVI has a good treatment effect on wastewater, can effectively degrade organic pollutants which are difficult to degrade in the wastewater, and has a certain application prospect on pretreatment of the wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of environmental protection, and in particular to application of starch-nano zero-valent iron in catalyzing electro-Fenton degradation of chemical wastewater. Background Art

[0002] The electro-Fenton technology is to generate H2O2 at the cathode when power is applied, and then react with Fe 2+ Fenton reaction occurs. •OH, which has strong oxidizing properties, can react with organic pollutants non-selectively, including dehydrogenation reaction, electron transfer reaction and C=C bond addition reaction, so that pollutants are rapidly degraded. 3+ It will also be reduced to Fe at the cathode 2+ , and continue to react with H2O2. In addition, physical processes such as electrosorption, anodic oxidation, and electrocoagulation also occur in this system, which also play a certain role in the degradation of pollutants.

[0003] The reaction mechanism of electro-Fenton is as follows:

[0004] O2+2H++2e - →H2O2;

[0005] Fe 2+ +H2O2+H + →Fe 3+ +H2O+·OH;

[0006] •OH+RH→R•+H2O;

[0007] Fe 3+ +e-→Fe 2+ .

[0008] The electro-Fenton method is based on H2O2 and Fe 2+ There are four different ways of generating :

[0009] (1) Electro-Fenton-iron oxidation method, Fe 2+ It is produced by oxidation of the iron plate of the anode, so it is also called the sacrificial anode method. H2O2 is added externally, and the two undergo a Fenton reaction to generate OH to react with organic pollutants. At the same time, the flocculation of Fe(OH)2 and Fe(OH)3 produced can also degrade some organic matter. The disadvantage is that H2O2 is added externally. H2O2 is corrosive and highly oxidizing, and its properties are unstable, so the cost of transportation and storage is increased.

[0010] (2) Electro-Fenton-H2O2 method: H2O2 reduces dissolved oxygen at the cathode to produce Fe 2+ It is added externally. In this method, in addition to the •OH produced by Fenton degrading pollutants, the anode will also oxidize some pollutants due to electrochemical action.

[0011] (3) Electro-Fenton-iron reduction method, in which H2O2 and Fe 2+ All are added from outside, Fe 2+ After reacting with H2O2, it will be oxidized to Fe 3+ , while Fe 3+ It will be reduced to Fe at the cathode 2+ , so the Fe 2+ It can be reused. The advantage of this method is that it does not produce a large amount of iron sludge.

[0012] (4) Electro-Fenton-Iron Oxidation-H2O2 method, in which Fe 2+ It is produced by oxidation of the iron plate at the anode, and H2O2 is produced by reduction of dissolved oxygen at the cathode.

[0013] It can be seen that although the electro-Fenton technology has the characteristics of simple operation, thorough treatment, and no subsequent pollution, and has been widely studied by researchers at home and abroad, it still has disadvantages such as high energy consumption, slow H2O2 generation efficiency, and high iron sludge production. Summary of the invention

[0014] The purpose of the present invention is to overcome at least one shortcoming of the prior art and provide an application of starch-nano zero-valent iron in catalyzing electro-Fenton degradation of chemical wastewater.

[0015] The technical solution adopted by the present invention is:

[0016] In a first aspect, the present invention provides a method for catalytic electro-Fenton degradation of chemical wastewater, wherein starch-nano zero-valent iron is added to the chemical wastewater to carry out Fenton oxidation reaction.

[0017] In some examples, the pH value of the Fenton oxidation reaction is 2-5.

[0018] In some examples, the reaction current of the Fenton oxidation reaction is 1-2A.

[0019] In some examples, the ratio of the added amount of starch-nano zero-valent iron to chemical wastewater is 1.25-3.75 g / L.

[0020] In some examples, the ratio of the addition amount of the starch-nano zero-valent iron to the chemical wastewater is 1.25 g / L, the pH value of the Fenton oxidation reaction is 3, and the reaction current is 1 A.

[0021] In some examples, the preparation method of starch-nano zero-valent iron includes the following steps: mixing and stirring a soluble ferrous salt solution and a starch suspension; adding a NaBH4 solution dropwise to the obtained mixed solution, continuing to stir the reaction, and selecting a precipitate by magnetic separation to obtain the starch-nano zero-valent iron.

[0022] In some examples, the mass fraction of starch in the starch suspension is 0.4% to 0.6%.

[0023] In some examples, the concentration of ferrous ions in the soluble ferrous salt solution is 0.19-0.21 mol / L.

[0024] In some examples, the volume ratio of the starch suspension to the soluble ferrous salt solution is 1:1.

[0025] In some examples, the concentration of the NaBH4 solution is 0.35-0.45 mol / L.

[0026] The beneficial effects of the present invention are:

[0027] 1) The present invention prepares starch-nano zero-valent iron (S-nZVI) and naked nano zero-valent iron (nZVI). Characterization methods such as SEM show that the prepared starch / nano zero-valent iron has more dispersed nanoparticles than nano zero-valent iron without starch addition, which solves the problem of easy agglomeration of traditional nano zero-valent iron nanoparticles to a certain extent, thereby improving its catalytic performance.

[0028] 2) Compared with the traditional Fenton method for treating chemical wastewater, the COD removal rate is higher, and S-nZVI can be collected and reused after reaction, which can reduce certain material costs.

[0029] 3) The wastewater before and after the reaction was analyzed by UV-visible spectroscopy and three-dimensional fluorescence spectroscopy. It was found that the electro-Fenton system with S-nZVI as the catalyst had a significant removal effect on organic pollutants such as benzene rings, unsaturated aldehydes, ketones, tyrosine, protein-like substances and humic acid in chemical wastewater, and the removal effect on cyclic aromatic compounds was also considerable.

[0030] 4) Experimental results show that the electro-Fenton system with S-nZVI as catalyst can remove most of the organic pollutants in chemical wastewater, especially those difficult to degrade and large molecular weight organic pollutants, effectively reduce the COD of chemical wastewater, which is helpful for subsequent secondary treatment and can be used as a pretreatment method for chemical wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 SEM images of nZVI (a), S-nZVI (b) and S-nZVI after catalytic reaction (c).

[0032] Figure 2 EDS images of nZVI (a), S-nZVI (b) and S-nZVI after catalytic reaction (c).

[0033] Figure 3XRD patterns of S-nZVI before and after catalytic reaction.

[0034] Figure 4 FT-IR graph of S-nZVI before and after catalytic reaction.

[0035] Figure 5 Fe 2p spectrum (a), O 1s spectrum (b) and total spectrum (c) before and after S-nZVI catalytic reaction.

[0036] Figure 6 This is the hysteresis loop of S-nZVI before and after the catalytic reaction.

[0037] Figure 7 The effect of reaction time on COD degradation rate.

[0038] Figure 8 This is the effect of S-nZVI dosage on COD degradation rate.

[0039] Fig. 9 This is the effect of the initial pH of the water sample on the COD degradation rate.

[0040] Fig.10 This is the effect of impressed current on COD degradation rate.

[0041] Fig.11 This paper compares the effects of S-nZVI catalytic electro-Fenton and traditional Fenton methods in treating chemical wastewater.

[0042] Fig.12 This is the UV-Vis absorption spectrum of chemical wastewater degradation in the S-nZVI catalytic electro-Fenton system.

[0043] Fig.13 Three-dimensional fluorescence spectra of water samples before (a) and after (b) treatment. DETAILED DESCRIPTION

[0044] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.

[0045] 1) Preparation of catalyst

[0046] 1.1 Preparation of S-nZVI catalyst

[0047] Prepare 0.5% corn starch suspension, 0.2 mol / L FeSO4 solution and 0.4 mol / L NaBH4 solution respectively. Mix 10 mL corn starch suspension and 10 mL FeSO4 solution and place on an electromagnetic stirrer for 30 min. Pour the NaBH4 solution into a burette. After the mixed solution is mixed for 30 min, drip the NaBH4 solution drop by drop into the mixed solution. When the first drop of NaBH4 solution is dripped into the mixed solution, the solution begins to turn black, proving that the reaction is rapid. After all the NaBH4 solution is dripped, continue stirring for 15 min and let stand for a few minutes. The generated corn starch / nano zero-valent iron will precipitate at the bottom. Use a strong magnet to absorb the newly generated S-nZVI, pour out the solution, rinse it repeatedly with ultrapure water several times, and then wash it three times with anhydrous ethanol. Filter out the black solid and dry it in a vacuum oven at 70 ° C for 12 h. Pay attention to sealing and drying when storing.

[0048] 1.2 Preparation of nZVI catalyst

[0049] The steps for preparing the nZVI catalyst are the same as those for preparing the S-nZVI catalyst, except that the corn starch suspension is not added.

[0050] 2) Electro-Fenton system for treating chemical wastewater

[0051] 2.1 Experimental Methods

[0052] The water sample studied in the present invention was taken from the chemical wastewater produced by a petrochemical company in Maoming, and the experimental study was carried out after diluting it 25 times. The water quality index analysis of the diluted chemical wastewater sample is shown in Table 1.

[0053] Table 1 Water quality indicators of chemical wastewater samples

[0054]

[0055] The specific experimental steps of the present invention are as follows: 400 mL of wastewater is taken into a reactor, and 35 mL of 0.5 mol / L Na2SO4 is added as an electrolyte to increase the conductivity of the reaction solution. The pH of the reaction solution is adjusted with dilute sulfuric acid and NaOH solution, and aeration is performed for 30 minutes before the reaction to ensure that the dissolved oxygen in the reaction solution is saturated. After aeration, the required amount of catalyst is added, the power supply is connected to start the reaction, and aeration and stirring are maintained during the reaction. Since the corn starch-nano zero-valent iron as a catalyst has strong magnetism, it is easy to adsorb it at the bottom of the reactor if a magnetic stirrer is used, and it cannot be well diffused in the reaction solution. To avoid this problem, this experiment uses an electric stirrer of model JJ-1A during the experiment.

[0056] The water samples were taken out every 30 minutes and the pH was adjusted to above 10 with NaOH solution in order to stop the reaction and reduce the Fe 2+ and Fe 3+ The solution was then filtered and the pH and COD of the filtrate were measured.

[0057] 3) Characterization and analysis of catalyst

[0058] 3.1 SEM and EDS analysis

[0059] In this experiment, SEM and EDS scanning and analysis were performed on nZVI without corn starch and S-nZVI before and after reaction. The analysis results are shown in Figure 1 and Figure 2 .

[0060] nZVI without added corn starch Figure 1 As shown in (a), some small particles in the figure aggregate to form large irregular particles with larger sizes. This is due to the electrostatic force between nanoparticles or the interaction of particle surface tension. nZVI has a tendency to aggregate without encapsulation. Therefore, it can be known that ordinary S-nZVI has a low surface area and poor reactivity. When these nZVI particles are coated with corn starch, it can bring positive effects. Its surface is coated with a layer of polymer molecules, which provides it with a strong spatial repulsion. The increase in the surface charge of the nanoparticles provides electrostatic stability, making the formed particles evenly dispersed and smaller in size, such as Figure 1 As shown in (b), the corn starch coating is evenly distributed on the surface of the nanoparticles, forming discrete, well-dispersed, and nearly spherical nanoparticles. Figure 1 (c) shows the S-nZVI after the reaction. In this figure we can see aggregated nanoparticles, which is due to the corrosion of the nanoparticles. This shows that the surface area of ​​the nanoparticles increases after being wrapped by corn starch, and the contact between the particles and the pollutants is enhanced.

[0061] EDS images of nZVI without corn starch and S-nZVI coated with corn starch are shown in Figure 2. Figure 2As shown in (a) and (b), the Fe content is the highest, 64.66% and 66.34% respectively, followed by the O content, 14.05% and 19.09% respectively. The high content of Fe indicates the formation of zero-valent iron. The presence of oxygen is due to the formation of an iron oxide layer on the surface of zero-valent iron. The O content on the surface of S-nZVI is higher than that of nZVI because of the hydroxyl groups in the starch molecules. This also proves that corn starch forms a coating on the nano zero-valent iron particles. The S content on the surface of the two is 4.35% and 3.61% respectively. The reason why S is contained is that the Fe source used in the preparation of nZVI and S-nZVI is FeSO4, and there is no calcination process in the preparation process, so S remains on its surface. Figure 2 (c) is the EDS image of S-nZVI after the reaction. It can be seen that the Fe content decreased from 66.34% to 58.42%, while the O content increased from 19.09% to 26.77%, which indicates the corrosion of the nanoparticles. The increase in O content may be due to the side reaction between S-nZVI and the dissolved oxygen in the reaction solution during the reaction, which is usually undesirable. This shows that although starch helps to increase the surface area and overall dispersibility of nanoparticles, it cannot prevent the side reaction of oxygen in the solution. It can be seen that starch can promote Fe by controlling the exposure of nanoparticles. 0 The electron transfer from the nucleus to the core cannot improve the selectivity of the nanoparticles for the reaction.

[0062] 3.2 XRD analysis

[0063] In order to explore the changes in the substances in S-nZVI before and after the reaction, this experiment used an X-ray diffractometer to scan and analyze S-nZVI before and after the reaction. The experimental results are shown in Figure 3 .

[0064] S-nZVI before the reaction Figure 3 As shown in the figure, the characteristic peak of zero-valent iron appears at a diffraction angle of 2θ of 44.8°, proving the presence of Fe, while another weak peak appears at a diffraction angle of 2θ of 35°, which is the characteristic peak of Fe2O3, indicating that an iron oxide shell is formed during the preparation of S-nZVI. The S-nZVI spectrum after the reaction shows that the characteristic peak of Fe at a diffraction angle of 2θ of 44.8° is significantly reduced, indicating that S-nZVI, as a catalyst and iron source, is actively participating in the Fenton reaction.

[0065] 3.3 FTIR analysis

[0066] In this experiment, FT-IR analysis was performed on S-nZVI and S-nZVI after reaction. The experimental results are as follows Figure 4 shown.

[0067] exist Figure 4The above is the FT-IR image of unreacted S-nZVI. It can be seen from the figure that 3229.8cm -1 and 1629.4cm -1 It is the absorption peak caused by the stretching vibration of hydroxyl groups. As we all know, each repeating unit of starch molecules contains hydroxyl groups, which is conducive to the complexation with nano zero-valent iron particles. -1 The absorption peak is caused by the CH stretching vibration of the COH- group. This is due to the presence of CH2OH in the starch molecule, which acts as a capping agent and helps prevent the aggregation of nanoparticles. -1 The peak at 654.9 cm is the CO bond, which is due to the presence of an acetal functional group (a carbon attached to two ether oxygens). -1 The peak at 602.1 cm represents the interaction of FeO-, which indicates that iron and starch interacted during the preparation of S-nZVI. -1 and 433.1cm -1 The absorption peak is caused by the stretching vibration of the phosphate group, which is because the starch molecule contains phosphate. It is precisely because of these functional groups in starch that the adsorption layer is formed, which plays a spatial shielding role and protects the nano zero-valent iron particles from getting close to each other.

[0068] Figure 4 The FT-IR image of S-nZVI after the reaction is shown below. It can be clearly seen that the absorption peaks have changed after the reaction, with many more absorption peaks, such as 1301.9 cm -1 The absorption peak caused by the stretching vibration of the ether bond (-COC-) and the absorption peak at 694.5 cm -1 The absorption peak caused by the stretching vibration of the CH bond is at 40°, which indicates that S-nZVI, in addition to its role as a catalyst and iron source, also has a certain adsorption effect on organic pollutants in chemical wastewater. Among the original absorption peaks, the absorption peak of hydroxyl group becomes wider, indicating that hydroxyl group has made a significant contribution to the reaction. The intensity of each original absorption peak has also decreased, indicating the attenuation of the functional groups in S-nZVI, which may be due to the aggregation of S-nZVI nanoparticles after the reaction.

[0069] 3.4 XPS analysis

[0070] In this experiment, an X-ray photoelectron spectrometer was used to scan and analyze S-nZVI before and after the reaction. The results are shown in Figure 5 .

[0071] from Figure 5 The overall spectrum in c shows that the main elements in S-nZVI are Fe, O, and C. Figure 5 Fe 2p spectrum of a Figure 1A total of 6 peaks were fitted, and the peaks at 707.2eV and 720.1eV binding energy represent Fe 0 The peaks at 710.9eV and 724.7eV binding energies represent Fe (II), and the peaks at 713.4eV and 728eV binding energies represent Fe (III). Figure 5 The O 1s spectrum of c was fitted with three peaks. The peaks at 530.1eV, 531.3eV, and 532.5eV binding energies represent OC=O, metal oxides, and O 2- The Fe(Ⅱ) in the Fe 2p spectrum before the reaction indicates that an oxide shell is formed outside the S-nZVI. The Fe(Ⅱ) in the Fe 2p spectrum after the reaction indicates that an oxide shell is formed outside the S-nZVI. 0 The sharp drop in the peak indicates that a large amount of iron on the surface of S-nZVI was dissolved during the reaction and actively participated in the reaction. The drop in OC=O after the reaction indicates that a complex reaction has occurred, proving that S-nZVI also has the function of adsorbing pollutants in wastewater.

[0072] 3.5 VSM analysis

[0073] In this experiment, a vibrating sample magnetometer was used to analyze the S-nZVI before and after the reaction. The hysteresis loops were shown in Figure 6 .

[0074] like Figure 6 As shown in the figure, the saturation magnetization intensity of S-nZVI before and after the reaction was measured under the condition of -10KOe to 10KOe and temperature of 298K, and the magnetization loop data of the magnetic response of S-nZVI particles before and after the reaction were analyzed to determine the saturation magnetization intensity. The saturation magnetization shows that the magnetic moment increases rapidly with the increase of the magnetic field. Obviously, S-nZVI before and after the reaction is superparamagnetic, which enables S-nZVI particles to respond quickly to the external magnetic field. From the magnetization curve, it can be seen that the saturation magnetization intensity of S-nZVI before and after the reaction is 69emu / g and 20emu / g, respectively, and the coercive force is 247Oe and 176Oe. The decrease in the saturation magnetization intensity of S-nZVI after the reaction may be because during the reaction, the S-nZVI particles react with the dissolved oxygen in the reaction solution to form a layer of iron oxide shell on their surface.

[0075] 4) Experimental analysis

[0076] 4.1 Effect of reaction time

[0077] Take 400mL of chemical wastewater in the reactor, add 0.5g of S-nZVI, adjust the pH of the reaction solution to 3 with 3mol / L H2SO4 solution, adjust the current to 1A, the corresponding voltage to 10V, and react for 180min. From the start of the reaction timing, take water samples at 30min, 60min, 90min, 120min, 150min, and 180min for COD determination. Three parallel experiments were performed to reduce errors. The experimental results are shown in Figure 7 .

[0078] like Figure 7 As shown, it can be seen that as the reaction proceeds, the COD of the treated wastewater gradually decreases. Within 90 minutes of the reaction, the COD of the wastewater degrades very quickly, with an average degradation rate of 64.89%. The degradation rate begins to slow down from 90 minutes to 120 minutes, and the degradation rate is completely flat after 120 minutes. In some reactions, the COD even increases. This is because the pH is 3 in the early stage of the reaction. Under acidic conditions, O2 is reduced to H2O2 in large quantities at the cathode, and Fe in S-nZVI is also oxidized to Fe 2+ At this time, the Fenton reaction becomes dominant, H2O2 and Fe 2+ The •OH generated by the reaction has a high oxidation potential and strong oxidizing property, which can quickly degrade organic pollutants in chemical wastewater. In the later stage of the reaction, due to the increase in pH, it gradually becomes unfavorable for the Fenton reaction to proceed, while H2O2 and Fe 2+ The reaction also generates Fe 3+ , Fe 2+ and Fe 3+ It will combine with the hydroxide ions in the solution to form Fe(OH)2 and Fe(OH)3 precipitates. These two precipitates will flocculate with the suspended matter and organic pollutants in the wastewater and precipitate together to reduce COD. It can be concluded that the reaction should not last too long, because after 120 minutes, the COD removal rate of the wastewater has basically leveled off. Continuing the reaction may cause a small increase in COD, which is not worth the loss. In addition, the useless increase in reaction time will not only waste precious time, but also cause a waste of electricity and an increase in operating costs. Therefore, the optimal reaction time is set at 120 minutes.

[0079] 4.2 Effect of S-nZVI dosage

[0080] In this experiment, S-nZVI played multiple roles. First, as a catalyst, it can accelerate the rate of H2O2 production at the cathode under acidic conditions, and the effect is visible to the naked eye. Second, as an iron source, it is oxidized to Fe at the anode. 2+, providing the necessary raw materials for the electro-Fenton reaction; thirdly, it can provide active sites for the solution to improve the efficiency of the reaction. 2+ They are all closely related to S-nZVI, so the dosage of S-nZVI should be studied to examine the effect of different S-nZVI filling amounts on the electro-Fenton treatment of chemical wastewater. The experimental conditions are as follows: take 400mL of wastewater to be treated in the reactor, adjust its pH to 3, add 0g, 0.3g, 0.5g, 1.0g, and 1.5g of S-nZVI to the reactor respectively, adjust the current to 1A, start the reaction, the reaction time is 120min, and take water samples for COD determination at 30min, 60min, 90min, and 120min respectively. The experimental results are shown in Figure 8 .

[0081] like Figure 8 As shown, when the dosage of S-nZVI is 0g, the COD removal rate of the treated wastewater is 23.53%. At this time, it may be that the dissolved oxygen is reduced to H2O2 at the cathode, which can degrade the organic pollutants in the chemical wastewater. When the dosage of S-nZVI increases to 0.3g and 0.5g, the COD removal rate of the treated wastewater reaches 60.68% and 76.03%. With the increase of S-nZVI dosage, the COD removal rate of chemical wastewater increases significantly. However, when the dosage of S-nZVI increases to 1.0g and 1.5g, the COD removal rate obtained is only 79.34% and 81.92%, which is not much different from the COD removal rate when the dosage of S-nZVI is 0.5g. This may be because excessive dosage of S-nZVI will lead to excessive Fe 2+ dissolves, while the initial Fe 2+ Too high a concentration will cause excess iron to be oxidized to Fe 3+ Therefore, considering both the economy and the effect, it was decided that the optimal condition was 0.5 g of S-nZVI.

[0082] 4.3 Effect of initial pH of water samples

[0083] pH is very important for the Fenton reaction. The Fenton reaction usually occurs under acidic conditions. Generally speaking, the optimal pH for the Fenton reaction is 3. In the Fenton reaction, if the pH is too high, Fe 2+ Will react with OH in the solution - Combined with Fe(OH)2, reducing the reaction rate; if the pH is too low, H2O2 will react with Fe 2+ The reaction generates another stable compound H3O2 +At the same time, if the pH is too low, H2O2 will decompose, which is not conducive to the Fenton reaction. Moreover, this experiment is an electro-Fenton experiment, Fe 2+ It comes from S-nZVI, H2O2 comes from the reduction of dissolved oxygen at the cathode, and the pH value also affects Fe 2+ The dissolution rate and H2O2 generation rate of the S-nZVI catalytic electro-Fenton system are required to study the effect of different initial pH on the treatment of chemical wastewater. The experimental conditions are as follows: 400 mL of chemical wastewater sample is placed in the reactor, and the initial pH of the reaction solution is adjusted with 3 mol / L H2SO4 solution and 1 mol / L NaOH solution. The S-nZVI dosage is 0.5 g, the applied current is 1 A, the reaction is 120 min, and samples are taken every 30 min to measure the COD. The experimental results are shown in Fig. 9 .

[0084] like Fig. 9 As shown in the figure, like the traditional Fenton reaction, the best reaction was achieved at pH = 3, and the COD removal rate of the treated wastewater reached 76.03%. At this time, there was enough H + , which can react with dissolved oxygen at the cathode to generate H2O2, greatly promoting the forward rate of the Fenton reaction and improving the treatment efficiency of the entire system. The COD degradation rates at pH = 2 and pH = 4 were only 65.39% and 57.80%, respectively. Whether the pH is high or low, H2O2 will decompose to varying degrees, and the rate of H2O2 generation at the cathode will decrease, thereby reducing the degradation efficiency of the entire system. When the water sample had an initial pH of 5, the COD removal rate rebounded to 63.54%, probably because under the condition of pH = 5, it is conducive to Cl - The reaction generates active chlorine, which also has strong oxidizing properties and can oxidize organic pollutants in wastewater. Although the Fenton reaction in the system is weakened, with the help of active chlorine, the degradation efficiency of the entire system has also recovered. Therefore, the initial pH of the water sample is selected as 3 as the optimal pH value for the S-nZVI catalytic electro-Fenton system to treat chemical wastewater.

[0085] 4.4 Effect of reaction current

[0086] Since the reaction in this experiment is an electro-Fenton reaction, Fe 2+ and H2O2 are produced at the anode and cathode respectively. The magnitude of the current has an influence on Fe 2+ and H2O2 generation rate plays a key role. In addition, the area of ​​the electrode in this experiment is constant, and the amount of current passing through a certain area of ​​the plate is limited. Therefore, when the current increases, the voltage between the two plates will also increase, so the cathode makes Fe 3+ Fe 2+The greater the conversion rate, the better it can promote the forward progress of the Fenton reaction and increase the reaction rate. However, if the current is too large, side reactions will occur at both electrodes, reducing the degradation efficiency of the entire system. For example, the generation of oxygen at the anode and the precipitation of hydrogen at the cathode will occur under high current conditions. As hydrogen is precipitated on the cathode, the pH of the solution will increase. From the above, it can be seen that too high a pH is not conducive to the Fenton reaction. Therefore, it is necessary to study the effect of applied current on the treatment of chemical wastewater by the electro-Fenton system. The experimental conditions are as follows: take 400 mL of chemical wastewater in a reactor, adjust the pH to 3, add 0.5 g S-nZVI to the reactor, adjust the applied current to 0.5 A, 1.0 A, 1.5 A, and 2.0 A respectively, react for 120 minutes, take samples at 30 minutes, 60 minutes, 90 minutes, and 120 minutes respectively, and determine their COD. The experimental results are as follows Fig.10 .

[0087] Fig.10 As shown in the figure, it can be seen that when the applied current increases from 0.5A to 1.0A, the COD removal rate of the treated wastewater increases from 52.05% to 76.03%. This is because the larger the applied current, the greater the voltage between the positive and negative electrodes. Within a certain range, the increase in voltage can increase Fe 2+ The dissolution rate and H2O2 generation rate of Fe 3+ Fe 2+ The reaction rate is accelerated, thereby increasing the rate of the Fenton reaction. However, when the applied current is increased from 1A to 2A, the COD removal rate of the treated wastewater drops from 76.03% to 66.73%. This is because the current is too large, which leads to the intensification of the side reactions of the two electrodes, and Fe 3+ Fe 2+ The advantages brought by the conversion will be covered up. The hydrogen evolution reaction at the cathode will cause the pH of the solution to increase, making the Fenton reaction no longer have suitable pH conditions. Excessive oxygen evolution at the anode will also cause the current efficiency to decrease. Therefore, this experiment selected the external reaction current of 1A as the optimal current for the S-nZVI catalytic electro-Fenton system to treat chemical wastewater.

[0088] 4.5 Comparison with traditional Fenton reaction

[0089] In order to demonstrate the advantages of the S-nZVI-constructed Fenton system in degrading chemical wastewater, a comparative test was conducted with the traditional Fenton method for treating chemical wastewater. The experimental conditions of S-nZVI-catalyzed electro-Fenton were: S-nZVI dosage 0.5g, external current 1A, initial pH=3, reaction time 12min. The experimental conditions of traditional Fenton were: c(Fe 2+ ): c (H2O2) = 1: 2, initial pH = 3, reaction time 120min. The reaction results are shown in Fig.11 .

[0090] exist Fig.11 As can be seen from the figure, the traditional Fenton reaction is rapid at the beginning because there are a lot of H2O2 and Fe in the solution at the beginning. 2+ The Fenton reaction is carried out vigorously, producing a large amount of •OH, which quickly degrades organic pollutants in chemical wastewater. However, in the middle and late stages of the reaction, a large amount of Fe 3+ , which increases the reverse reaction rate of the Fenton reaction, produces less •OH, and reduces the degradation efficiency of chemical wastewater. At 120 minutes, it can be clearly seen that the COD elimination rate of S-nZVI catalytic electro-Fenton has significantly exceeded the COD elimination rate of traditional Fenton. Although the COD treatment rate of this experimental method is not very advantageous over the traditional Fenton method for treating chemical wastewater, the S-nZVI used in this experimental method can be collected by magnetic absorption with a strong magnet after the reaction, and then continue to be used. After three reuse experiments, the effect is not much different from that of the first use, so the material cost of this method is greatly reduced.

[0091] 4.6 UV-Vis spectroscopy

[0092] In order to verify the degradation effect of S-nZVI catalytic electro-Fenton system on chemical wastewater, the original water sample and the water samples after reaction for 30min, 60min, 90min, and 120min were diluted 10 times, and then the water samples were scanned at a wavelength of 200~800nm ​​using a UV-visible spectrometer. The experimental conditions of the water sample were: S-nZVI dosage of 0.5g, external current of 1A, initial pH of the water sample of 3, and treatment time of 120min. The scanning results are shown in Figure 2. Fig.12 .

[0093] Analysis of the UV-visible spectra of the water samples in the figure shows that the raw water sample of the untreated chemical wastewater has a strong absorption peak at 200nm, which is a cyclic aromatic compound, and there is a more obvious absorption peak near 275nm, which may be the absorption peak of benzene ring or unsaturated aldehydes, ketones and other substances. It can be seen from the figure that the intensity of the absorption peak of the water samples with different treatment times is different and has been decreasing, and the intensity of the absorption peak of the water sample after only 30 minutes of reaction has been greatly reduced compared with the original water sample. It can be considered that after 30 minutes of reaction, a large number of easily degradable organic pollutants in the chemical wastewater have been mostly degraded. After 120 minutes of reaction, the absorption peak of 275-800nm ​​has basically disappeared, leaving only a small absorption peak near 200nm, indicating that benzene rings or unsaturated aldehydes, ketones and other substances with absorption peaks in this wavelength have been basically removed, leaving only a few cyclic aromatic compounds, which is also consistent with the chromaticity change of the water sample after 120 minutes of chemical wastewater treatment.

[0094] The analysis shows that after 120 minutes of treatment of chemical wastewater by the S-nZVI catalytic electro-Fenton system, only cyclic aromatic compounds and a very small amount of benzene rings or unsaturated aldehydes and ketones remain in the water sample, indicating that this method has a significant effect on the degradation of benzene rings or unsaturated aldehydes, ketones and other substances in chemical wastewater, and also has a good degradation effect on cyclic aromatic compounds. In general, the degradation effect on organic pollutants is obvious.

[0095] 4.7 Three-dimensional fluorescence spectroscopy analysis

[0096] In this experiment, a three-dimensional fluorescence spectrometer was used to scan and analyze the water samples before and after the reaction. The results are shown in Fig.13 .

[0097] from Fig.13 As can be seen in (a), the two fluorescence peaks of the chemical wastewater before the reaction are 270nm / 305nm and 320nm / 390nm, respectively, called a and b. Therefore, the organic pollutants in the chemical wastewater used in this experiment are mainly distributed in regions IV and V. Region IV is tyrosine and protein-like, and region V is humic acid. Therefore, it can be known that these two substances are the main organic pollutants in the chemical wastewater used in this experiment. Fig.13 (b) is the effluent after 120 minutes of reaction. It can be clearly seen that the two peaks a and b in the raw water have basically disappeared, indicating that most of the organic pollutants in zones IV and V can be removed by this experimental method. This method is ideal for treating chemical wastewater.

[0098] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.

Claims

1. A method for catalytic electro-Fenton degradation of chemical wastewater, characterized in that: Starch-nano zero-valent iron was added to chemical wastewater to carry out Fenton oxidation reaction.

2. The method according to claim 1, characterized in that The pH value of the Fenton oxidation reaction is 2-5.

3. The method according to claim 1, characterized in that The reaction current of the Fenton oxidation reaction is 1-2A.

4. The method according to claim 1, characterized in that: The ratio of the added amount of starch-nano zero-valent iron to chemical wastewater is 1.25-3.75 g / L.

5. The method according to any one of claims 2 to 4, characterized in that: The ratio of the addition amount of starch-nano zero-valent iron to chemical wastewater is 1.25 g / L, the pH value of the Fenton oxidation reaction is 3, and the reaction current is 1 A.

6. The method according to claim 1, characterized in that The preparation method of starch-nano zero-valent iron comprises the following steps: 1) Mix and stir the soluble ferrous salt solution and starch suspension; 2) Adding NaBH4 solution dropwise into the mixed solution obtained in step 1), continuing to stir the reaction, and selecting the precipitate by magnetic separation to obtain the starch-nano zero-valent iron.

7. The method according to claim 6, characterized in that The mass fraction of starch in the starch suspension is 0.4% to 0.6%.

8. The method according to claim 6, characterized in that The concentration of ferrous ions in the soluble ferrous salt solution is 0.19-0.21 mol / L.

9. The method according to claim 7 or 8, characterized in that: The volume ratio of the starch suspension to the soluble ferrous salt solution is 1:

1.

10. The method according to claim 6, characterized in that The concentration of the NaBH4 solution is 0.35-0.45 mol / L.

Citation Information

Patent Citations

  • Quick preparation method for starch-stabilizing nanometer zero-valent iron

    CN104722777A

  • Method for degrading organic pollutants through synergistic catalysis of ferric salt and zero-valent iron

    CN112174288A

  • Three-dimensional heterogeneous electro-Fenton device and application

    CN114804300A